Analysis of shear wall structure in Pulau Pinang due to wind load and long distance Sumatran earthquake in terms of stiffness of the building / Mohd Hafiz Kadir - Kadir, Mohd Hafiz (2007)
Long-distance earthquakes generated from Sumatra and Java has been a cause for concern in recent years for countries in the Indo-China region including Singapore, Malaysia and Thailand. The recent OFF THE WEST COAST OF NORTHERN SUMATRAN earthquake (on 26th December 2004), which measured a moment magnitude of 9.1 and the latest, SOUTH OF JAVA, INDONESIA earthquake (on 17 July 2006) with magnitude of 7.7, was widely felt in Malaysia especially in Penang from the epicenter of the earthquake. High-rise structure is essentially a vertical cantilever that is subjected to axial loading by gravity and to transverse loading by lateral load such as wind or earthquake. It is common to design high-rise building structures with shear walls to resist horizontal loads such as wind or seismic loads Tall building will deflect when the building is subjected to lateral load such as wind load and seismic loads. BS6399 (PART 2):1995 and Uniform Building Code (UBC):1994 are used to determine wind force and seismic force respectively. In this study the effect of the lateral load on deflection for overall height and inter storey of the propose building will be considered. To determine the deflection, finite element software, LUSAS is used in this study. The control model is built according to selected floor plan which consists of 10 storey building. The result of the control model is compared with the empirical method to make sure the accuracy of the model. Then the model is extended to several models with different height i.e. 15, 20, 25, 30 and 35 stories. The deflection for first 5 models is satisfied and adequate for overall and floor-to-floor drift but not for the last model. The relationship between stiffness in terms of flexural rigidity (EI) and deflection is defined in this study by the logarithmic equation y = 2E+12Ln(x) + 1E+13, where Y represent the total EI values and X represent the maximum deflection for the shear wall structure.